Impermeability evaluation of concrete with fly ash aggregate and prediction with modelling - Lalitha, Gurikini; Reddy, Chilukala Ritvik (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Concrete is the most synthesized material in construction sector which it has aggregate as one of its components. The use of natural aggregate in concrete preparation uses a significant amount of non-renewable resources and energy, having a significant environmental impact. Multiple research projects have been conducted to safeguard natural reserves, seeking a solution to the waste disposal issue, and reduce construction costs by utilizing waste materials. FA(Fly Ash) aggregate is one such material that can be a replacement for natural aggregate.
Keywords: FA (Fly Ash) aggregate; Durability properties; Support-vector-machine (SVM); Prediction models; Coefficient of Determination (R2)